The protective effect of trehalose and monosodium glutamate on yeast viability and antagonistic properties during freeze-drying - Joanna Krzymińska; Jolanta Kowalska (Journal of Plant Protection Research)
In the present eco-conscious era, consumers opt for food choices reflecting ethical and environmental concerns, which increases the demand for organic products. Biocontrol is a viable plant protection method in organic farming. Freeze-drying is a long-term preservation technique for microbial agents, ensuring their genetic stability and viability. To reduce freeze-drying-induced damage to their cells, cryoprotective agents like trehalose and monosodium glutamate are used. This study evaluated the impact of the addition of these substances during the freeze-drying process on chosen yeast isolates’ viability, their ability to survive on tomato leaves and maintain antagonistic properties against Botrytis cinerea Pers. Yeast isolates 114/73 (Wickerhamomyces anomalus E.C. Hansen) and 117/10 (Naganishia albidosimilis Vishniac & Kurtzman) were tested on tomato plants under greenhouse conditions before and after the freeze-drying process for both the ability to colonize leaves and as a preventive and interventional treatment against B. cinerea. Yeast viability post freeze-drying was evaluated in vitro. Both trehalose and monosodium glutamate increased yeast viability during the freeze-drying process. Viability was not very high (from 30.33 to 36.17% for 117/10 and from 10.67 to 16.5% for 114/73). Yeast dehydrated after freeze-drying, protected with trehalose and monosodium glutamate, displayed the same colony count on tomato leaves as before freeze-drying. The efficacy of protective treatments depended on the yeast isolate, the protective substance used during freeze-drying, treatment timing (prevention vs. intervention), and interactions of those factors. Cryopreserved isolate 117/10 performed better than 114/73 with the addition of either trehalose or monosodium glutamate, reducing the disease severity index from 88.3% (control) to 18.75−55.33%. Preventive treatments were more efficient than intervention. The leaf colonization ability and biocontrol efficacy of yeast isolates against B. cinerea post-freeze-drying offer promising solutions in sustainable agriculture. However, further research, to analyze the interactions between various factors and to optimize strategies may be needed.